Screening of Quality Markers During the Processing of Reynoutria multiflora Based on the UHPLC-Q-Exactive Plus Orbitrap MS/MS Metabolomic Method - Bai, Junqi; Su, He; Liang, Youling; Shi, Xuhua; Huang, Juan; Xu, Wen; Zhang, Jing; Gong, Lu; Huang, Zhihai; Qiu, Xiaohui (Frontiers in Pharmacology, 2021)
The root of Reynoutria multiflora (Thunb.) Moldenke (syn.: Polygonum multiflorum Thunb.) is a distinguished herb that has been popularly used in traditional Chinese medicine. The raw Reynoutria multiflora (RRM) should be processed by steaming before use, the processing time is not specified in the processing specification. Our previous studies showed that the efficacy and toxicity of processed Reynoutria multiflora (PRM) at different processing time were inconsistent. A comprehensive identification method was established in this study to find quality marker of raw Reynoutria multiflora (RRM) and processed Reynoutria multiflora (PRM) with different processing times. Metabolomics based on ultra-high-performance liquid chromatography tandem quadrupole/electrostatic field orbitrap high-resolution mass spectrometry (UHPLC-Q-Exactive plus orbitrap MS/MS) was used in this study. Using the CD.2 software processed database, multivariate statistical analysis methods coupled with cluster analysis and heatmap were implemented to distinguish between RRMs and PRMs with different processing times. The results showed that RRM and PRMs processed for 4 h, 8 h, 12 h, and 18 h cluster into group 1, and PRM processed for 24 h and 32 h into group 2, indicating that it can effectively distinguish between the two groups and twenty potential markers made the highest contributions to the observed chemical differences between two groups. Among them, tetrahydroxystilbene-O-hexoside-O-galloyl and sucrose can be used to identify PRM processed for 24 h. Therefore, the properties of RRM changed after 24 h of processing, and the quality markers were screened to distinguish RRM and PPM, it can also be used as an important control technology for the processing of RM, which has wide application prospects.